Spain : NCL meeting (notes)
015b_0022_001 N.C.L. Mtg. Spain 22 Dec 1936 Grenfell (1) Defence situation serious. (2) Food problem growing acute (3) Send British observer. (4) Non-Intervention enable Spain Gov to win. (5) Must feed people by sea routes. (6) Send food openly from Britain. (7) Continue help for Ambulances. (8) Shortage of anaesthetics Bevin Get C.W.S to take orders for food. Send ships with these. Approach Spanish Gov for [ ] of a/c. Individual unions would help by loans [shorthand] Jarrow (Hays Wharf) [shorthand] Get printed circulars of what TUC & Int Fund has done - Make un Confidential (Illustrate this) Read at Meetings Volunteers. Consultation re policy for effective stopping of Volunteers. 292/946/15b/22